Penggunaan Asap Cair terhadap Kualitas Fisik dan Mikrobiologis Daging Broiler. - Andy, Andy; Warangkiran, Eklesia Dian Milenia; Aulyani, Tutik Lusyta; Azhar, M.; Sangkek, Miksen Merko; Kusuma, Satria Budi (BPFP Universitas Bengkulu, 2024)
The aim of this research was to determine the effect of marinating broiler meat using liquid smoke on the physical and microbiological quality of broiler meat at various concentrations. The research was carried out at the Gowa Polbangtan Product Processing Laboratory and the BBVet Maros Laboratory. The research was carried out using a Completely Randomized Anova Design followed by the Duncan test, with 4 treatments, namely: P0: (Control), P1: 1% liquid smoke, P2: 2% liquid smoke, P3: 3% liquid smoke and 4 repetitions with parameters pH, Total Bacteria and Beginning of Decay. Based on the test results, it shows that the concentration of liquid smoke has no significant effect on pH and the start of decay. However, it affects total bacteria. Marinating meat with liquid smoke up to a concentration of 2% showed the lowest total bacteria compared to other treatments. Keywords: Liquid Smoke, Broiler Meat, Beginning of Decay, pH.